2008
DOI: 10.1002/cmdc.200700176
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease (GERD): Is There More to the Story?

Abstract: Gastroesophageal reflux disease (GERD) affects both men and women worldwide, with the most common symptom of GERD being frequent heartburn. If left untreated, more serious diseases including esophagitis and/or esophageal cancer may result. GERD has been commonly held to be the result of gastric acid refluxing into the esophagus. Recent work, however, has shown that there are acid-producing cells in the upper aerodigestive tract. In addition, acid-producing bacteria located within the upper gastrointestinal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…The H + /K + -ATPase pump is classified as a member of the P-type, or ion-motive-phosphorylating, ATPase family because the ion transport of this particular proton pump is coupled to a cycle of phosphorylation and dephosphorylation. (For a more detailed explanation of the gastric H + /K + -ATPase, and its involvement in acid production and regulation, the reader is again directed to our recent review [7].) P-type ATPases are not restricted to only gastric proton pumps in humans; a number of non-gastric H + /K + -ATPases, Na + /K + -ATPases, and Ca 2+ -ATPases are also members of the P-type family [7,20,21,29].…”
Section: Proton Pumps In Humans Bacteria and Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…The H + /K + -ATPase pump is classified as a member of the P-type, or ion-motive-phosphorylating, ATPase family because the ion transport of this particular proton pump is coupled to a cycle of phosphorylation and dephosphorylation. (For a more detailed explanation of the gastric H + /K + -ATPase, and its involvement in acid production and regulation, the reader is again directed to our recent review [7].) P-type ATPases are not restricted to only gastric proton pumps in humans; a number of non-gastric H + /K + -ATPases, Na + /K + -ATPases, and Ca 2+ -ATPases are also members of the P-type family [7,20,21,29].…”
Section: Proton Pumps In Humans Bacteria and Fungimentioning
confidence: 99%
“…Consequently, GERD patients are treated with PPIs on a continuous basis, even when no symptoms are present. While the PPIs are designed to mechanistically shut off the H + /K + -ATPase proton pumps of parietal cells in the stomach, evidence has shown that other human tissues also contain cells possessing the H + /K + -ATPase enzyme [7,[20][21][22][23][24]. Furthermore, commensal acid-producing bacteria have been found in the stomach, upper aerodigestive tract, and oral cavity [25,26].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the stomach, gastric acid is produced by the parietal cells located in the lining of the stomach through the action of H + /K + -ATPase, known as the gastric proton pump [10]. Regulation of stomach pH is a complex process that includes stimulation by gastrin, histamine, and acetylcholine ( Figure 1) [10][11][12].…”
Section: Pathophysiology Of Acid-related Gastrointestinal Disordersmentioning
confidence: 99%
“…Regulation of stomach pH is a complex process that includes stimulation by gastrin, histamine, and acetylcholine ( Figure 1) [10][11][12]. Secretion of gastric acid is evoked by a number of physiologic stimuli, including the presence of food in the stomach or intestines, or merely the taste, smell, or thought of food [10][11][12]. Proton pump inhibitors block the last stage of acid production and secretion of acid into the lumen of the stomach by inhibiting the action of the gastric proton pump, causing a rise in the gastric pH ( Figure 1) [12].…”
Section: Pathophysiology Of Acid-related Gastrointestinal Disordersmentioning
confidence: 99%